A Review on the Present Marketing Mix Applies Particularly to the Marketing: Examining the Current Marketing Mix and its Implementation (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The key purpose of this research is to examine, in specific, the current marketing combination. This research gives advertisers an insight which can be used as strategies to help them achieve their marketing goals. Borden (1965) states that he was the first one to use the word marketing combination and Culliton proposed it to him (1948). McCarthy (1964) offered the 4Ps Marketing Blend as a way of implementing Marketing Planning (Bennett, 1997). The marketing mix is based on a single microeconomic theory P (price) (Chong, 2003). In order to face up to a highly dynamic landscape new Ps were put onto the marketing scene. Also, by analysing scholarly views from five marketing management subdivisions (consumer marketing, partnership marketing, service marketing, retail marketing and industrial marketing) and new marketing disciplines Möller (2006) provides an updated image of the current situation in Mix discussion as a marketing model and dominant marketing management method (E-Commerce). Numerous research, including Lauterborn (1990), Möller (2006), Popovic (2006) and Fakeideas, have criticised the definition of 4Ps (2008). However, the 4Ps remain a cornerstone of the marketing mix, notwithstanding their shortcomings. The following Ps are also needed to reach an understanding on eligibility and realistic implementation (Kent and Brown, 2006).